Study On The Egg Salting Process Using Reverse Osmosis Method At Various Immersion Times - Roni Kastaman; . Sudaryanto; Budi Herdi Nopianto (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
The eggs salting process is one type of egg preservation and handling technique which is relatively simple and low-cost method, but needs a long immersion time to obtain a good salted egg characteristics. The objective of this research was to study the re